If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65x = 110x Solving 65x = 110x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-110x' to each side of the equation. 65x + -110x = 110x + -110x Combine like terms: 65x + -110x = -45x -45x = 110x + -110x Combine like terms: 110x + -110x = 0 -45x = 0 Divide each side by '-45'. x = 0 Simplifying x = 0
| 12x+y=59 | | 10+7x=21-4x | | 11-5x=2-7x | | (3x/2)-x=(x/6)-(4/3) | | (3x/32)-x=(x/6)-(4/3) | | 3x+8=2.5x | | 13x^2+4-[5(x^2-7)+8]= | | 50x+14x=40 | | log2(sqrt(42/36)) | | (8+4i)(-6-7i)= | | x^2-4x+1.75=0 | | 3LN(5x+8)=30 | | 8x+30=1000 | | 10=10e(2*k) | | w^4-2w^2+2=0 | | 250y+61x=68find | | 20=10e^2k | | 250y+61x=68 | | 3x=4.86 | | (x^2-36)/(x^2-216) | | 281x^2-512x-2448=0 | | y^4=8x | | 3-9x+5y-15xy=0 | | lny=lna+xlnb | | 9x-5y^2=25whatisy | | 3x-5y=6whatisxy | | 9x-25y^2=25 | | y=x^2+x+0.25 | | 4m^2-4m-7=0 | | 10r^2-13r-3=0 | | 3x+y+4z=0 | | g(x)=5x^2-2(4x-3) |